Cholera outbreak in some communities in North-East Nigeria, 2019: an unmatched case-control study - Idowu O. Fagbamila; Muhammad A. Abdulkarim; Mabel K. Aworh; Belinda Uba; Muhammad S. Balogun; Patrick Nguku; Ajibji Y. Gandi; Ibrahim Abdullahi; Emmanuel C. Okolocha; Jacob K. P. Kwaga; Ndadilnasiya E. Waziri (BMC, 2023)
Abstract Background Cholera, a diarrheal disease caused by the bacterium Vibrio cholerae, transmitted through fecal contamination of water or food remains an ever-present risk in many countries, especially where water supply, sanitation, food safety, and hygiene are inadequate. A cholera outbreak was reported in Bauchi State, North-eastern Nigeria. We investigated the outbreak to determine the extent and assess risk factors associated with the outbreak. Methods We conducted a descriptive analysis of suspected cholera cases to determine the fatality rate (CFR), attack rate (AR), and trends/patterns of the outbreak. We also conducted a 1:2 unmatched case-control study to assess risk factors amongst 110 confirmed cases and 220 uninfected individuals (controls). We defined a suspected case as any person > 5 years with acute watery diarrhea with/without vomiting; a confirmed case as any suspected case in which there was laboratory isolation of Vibrio cholerae O1 or O139 from the stool while control was any uninfected individual with close contact (same household) with a confirmed case. Children under 5 were not included in the case definition however, samples from this age group were collected where such symptoms had occurred and line-listed separately. Data were collected with an interviewer-administered questionnaire and analyzed using Epi-info and Microsoft excel for frequencies, proportions, bivariate and multivariate analysis at a 95% confidence interval. Results A total of 9725 cases were line-listed with a CFR of 0.3% in the state. Dass LGA had the highest CFR (14.3%) while Bauchi LGA recorded the highest AR of 1,830 cases per 100,000 persons. Factors significantly associated with cholera infection were attending social gatherings (aOR = 2.04, 95% CI = 1.16-3.59) and drinking unsafe water (aOR = 1.74, 95% CI = 1.07-2.83). Conclusion Attending social gatherings and drinking unsafe water were risk factors for cholera infection. Public health actions included chlorination of wells and distribution of water guard (1% chlorine solution) bottles to households and public education on cholera prevention. We recommend the provision of safe drinking water by the government as well as improved sanitary and hygienic conditions for citizens of the state.